Novel method for the isolation of adipose stem cells (ASCs) - Rada, Tommaso (2009)
Adipose stem cells (ASCs) represent a cell population with great potential for tissue engineering applications. Several articles have been published showing the proliferation and differentiation potential, the markers and the wide range of potential applications of these cells. In the majority of these studies the ASCs are isolated using a basic enzymatic procedure, which results in a quite heterogeneous cell population that compromises their proliferation and differentiation. This paper reports the development and optimization of a new isolation/purification method that allows populations of ASCs to be obtained, which significantly reduces (and eventually eliminates) the ‘contamination’ of other cell types. This method is based on the use of immunomagnetic beads coated with specific antibodies. The first part of the study described here analysed the expression of marker genes for stem cells and the colony-forming unit (CFU) capacity of the cells isolated, while the second part is dedicated to the osteogenic differentiation potential of the isolated cells. The results showed that, using the isolation method based on immunomagnetic beads, it was possible to obtain ASCs and also underline the existence of several subpopulations of stem cells in the adipose tissue.